Large animal models and new therapies for glycogen storage disease. Issue 3 (16th September 2014) - Brooks, Elizabeth D.; Koeberl, Dwight D.
Abstract: Glycogen storage diseases (GSD), a unique category of inherited metabolic disorders, were first described early in the twentieth century. Since then, the biochemical and genetic bases of these disorders have been determined, and an increasing number of animal models for GSD have become available. At least seven large mammalian models have been developed for laboratory research on GSDs. These models have facilitated the development of new therapies, including gene therapy, which are undergoing clinical translation. For example, gene therapy prolonged survival and prevented hypoglycemia during fasting for greater than one year in dogs with GSD type Ia, and the need for periodic re‐administration to maintain efficacy was demonstrated in that dog model. The further development of gene therapy could provide curative therapy for patients with GSD and other inherited metabolic disorders.